Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. The degree to which school principals practice the values of integrity from the point of view of female deputies in Taif Governorate Co-Prof. Saleha Hai Al-Sofiani 2. The impact of online educational service quality on the reputation of Dubai University during the COVID-19 pandemic from the perspective of students Mr. Abdelmuttaleb Abdelsalam Elomari 3. Teachers’ and Parents’ Attitudes Towards the Motives for Privatizing Education in Arab Private Schools in the Haifa and Upper Galilee Areas Dr. Lubna Ali Elenat Khalaily 4. Training needs for the Madrasati platform from the point of view of principals of general education schools in Al-Kharj Governorate Ms. Nouf Fahad Almuayli 5. The extent to which the standards of the Commission for International Accreditation across regions (CITA) can be applied in leading schools in Jeddah from the perspective of leading school principals Dr. Majed Atteah Al-Sulami,Prof. Abdul-Hayy Ahmed Al-Subaihi 6. Artificial Intelligence and its Impact on the Quality of English Language Teaching: An Applied Study on English Language Teachers in Primary Schools - Asir Region Ms. Aliah Mohammed Alahmari 7. Anxiety as a Mediator between Procrastination and Work Engagement for Administrators Ms. Alhanoof Mansour Alluhaidan., Dr. Ahmed Mohammed Ahmed Alhussein 8. Emotional intelligence and its relationship to some variables among kindergarten teachers city of Najran Dr. Nada Izzeldeen Jafar